2018
DOI: 10.5014/ajot.2018.023648
|View full text |Cite
|
Sign up to set email alerts
|

Goal Attainment and Goal Adjustment of Older Adults During Person-Directed Cancer Rehabilitation

Abstract: Although most participants were able to meet their goals, many also changed their goals and priorities after reflection and attempts to resume or initiate meaningful activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…Aims of the mixed methods studies (n = 11) could be broadly categorized as: intervention development (Arends et al, 2015(Arends et al, , 2017Scobbie et al, 2011), process evaluation (Lyons et al, 2018;McPherson et al, 2009;Scobbie et al, 2013); understanding the process of goal adjustment in different long-term conditions (Boerner & Cimarolli, 2005;Boerner & Wang, 2012;Crombez et al, 2016;Hoyt et al, 2016) and investigating goal setting issues in neurological rehabilitation (Playford et al, 2009).…”
Section: Mapping Of Goal Adjustment Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Aims of the mixed methods studies (n = 11) could be broadly categorized as: intervention development (Arends et al, 2015(Arends et al, , 2017Scobbie et al, 2011), process evaluation (Lyons et al, 2018;McPherson et al, 2009;Scobbie et al, 2013); understanding the process of goal adjustment in different long-term conditions (Boerner & Cimarolli, 2005;Boerner & Wang, 2012;Crombez et al, 2016;Hoyt et al, 2016) and investigating goal setting issues in neurological rehabilitation (Playford et al, 2009).…”
Section: Mapping Of Goal Adjustment Literaturementioning
confidence: 99%
“…The "E" in the SMARTER framework denotes "evolving", acknowledging that goals can be fluid, changing and dynamic. The Health Through Activity programme (Lyons et al, 2018) is an educational, goal based, intervention. The need for goal adjustment, disengagement and reengagement is considered in a weekly goal review.…”
Section: Synthesis Of the Goal Adjustment Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent cognitive rehabilitation guidelines suggest integrating cognitive training together with individualised goal-directed interventions aimed at promoting occupational functioning (Cicerone et al., 2019). Furthermore, the results of several pilot studies implementing occupation-based treatment among cancer survivors found promising results (Lyons et al., 2018; Newman et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of outcomes of rehabilitation must take into account the heterogeneity among patients in type of deficits and goals for treatment. A goal attainment approach has been widely used in rehabilitation and other types of treatment when there is heterogeneity in desired outcomes (Lyons et al, 2018;Turner-Stokes, 2009). Specifically, goals for various aspects of function are selected at the outset of rehabilitation, including the level of performance expected at the completion of treatment.…”
mentioning
confidence: 99%